The Role of the North Sumatra DPRD in Improving Community Welfare Through Public Policy - Wahyu Wiji Utomo; Rahmat Affandi; Najwa El-Khoir Hasibuan; Nafisa Agda Maghrusyah; Rizki Fadilah Nasution; Batara Harahap; Roni Rahmat Ritonga (Public Policy: Jurnal Ilmu Sosial dan Kebijakan, 2026)
This study aims to analyze the strategic role of the Regional House of Representatives (DPRD) of North Sumatra in improving community welfare through public policies. The DPRD's legislative, budgeting, and supervisory functions contribute to the creation of policies that support social and economic development. This research employs a qualitative approach with a descriptive analysis method, utilizing primary data from interviews with policymakers and secondary data from relevant official documents. The findings reveal that the DPRD actively formulates inclusive public policies, such as budget allocations for education, healthcare, and infrastructure sectors. However, challenges such as limited institutional capacity and political influences may hinder policy effectiveness. Therefore, enhancing the quality of DPRD human resources, ensuring transparency, and increasing public participation in the legislative process are necessary to achieve more targeted policies. This research is expected to serve as a reference to strengthen the DPRD’s role in developing public policies oriented towards community welfare.